PENGEMBANGAN SUMBER DAYA PENDIDIK DI MA BUSTANUL ULUM JAYASAKTI LAMPUNG TENGAH - GUNAWAN, MUMAMAD RIFKI; HADIATI, ETI; AYU, SOVIA MAS (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
In the era of globalization, education is the main pillar in community development, including in Indonesia. The development of human resources (HR) in educational institutions is very important to improve the quality of education and overcome the challenges of the times. This research aims to analyze the development of educational resources at Madrasah Aliyah (MA) Bustanul Ulum Jayasakti, Central Lampung. The method used is a descriptive qualitative approach with case studies, involving in-depth interviews, direct observation and document analysis. The research results show that MA Bustan Ulum implements strategic development planning through three curricula government curriculum, Gontor Islamic boarding school, and Salaf Islamic boarding school which provides comprehensive understanding to educators. In addition, school initiatives to increase productivity and career opportunities for educators through training programs, although still limited, demonstrate commitment to human resource development. The results of this research enrich understanding of best practices in human resource development and can be used as a model for other educational institutions in their efforts to improve the quality of education in a sustainable manner. ABSTRAKDalam era globalisasi, pendidikan menjadi pilar utama dalam pembangunan masyarakat, termasuk di Indonesia. Pengembangan sumber daya manusia (SDM) di lembaga pendidikan sangat penting untuk meningkatkan kualitas pendidikan dan mengatasi tantangan zaman. Penelitian ini bertujuan untuk menganalisis pengembangan sumber daya pendidik di Madrasah Aliyah (MA) Bustanul Ulum Jayasakti, Lampung Tengah. Metode yang digunakan adalah pendekatan kualitatif deskriptif dengan studi kasus, melibatkan wawancara mendalam, observasi langsung, dan analisis dokumen. Hasil penelitian menunjukkan bahwa MA Bustan Ulum menerapkan perencanaan pengembangan yang strategis melalui tiga kurikulum kurikulum pemerintah, pesantren Gontor, dan pesantren salaf yang memberikan pemahaman komprehensif kepada pendidik. Selain itu, inisiatif sekolah untuk meningkatkan produktivitas dan peluang karir pendidik melalui program pelatihan, meskipun masih terbatas, menunjukkan komitmen terhadap pengembangan SDM. Hasil penelitian ini memperkaya pemahaman tentang praktik terbaik dalam pengembangan SDM dan dapat dijadikan model bagi lembaga pendidikan lainnya dalam upaya meningkatkan kualitas pendidikan secara berkelanjutan.